KERAGAAN VARIETAS PADI SAWAH DI LAHAN MARGINAL LAMPUNG - Setyo Jatmoko; Ishak Juarsah (Jurnal WACANA PERTANIAN, 2019)
Acid dry land in the experimental garden Taman Bogo, East Lampung including the classification of Ultisol acil, and generally ultisol acid soils can be used as representative for acid soils in Indonesia.  Characteristic of ultisol soil, among others: sour soil reaction (low pH <5.5), high aluminium content, high P fixation, exchangeable base contents and low exchange capacity (CEC), iron and manganese content close to poisonning, sensitive erosion and poor biotic elements. Acid dry land in Indonesia is directed in supporting the improvement of land resources, Display/ Show window and visitor plot development of acid dry land management technology, implemented to accelerate the process of superior technology transfer such as fertilizer technology and the use of organic materials, conservation, reclamation and land rehabilitation, as well as superior varieties in acid dry land.  Show window dan visitor plot  development of dry land management technology in Taman Bogo experimental garden is a means of discussion and communication between researchers, extension workers, farmers and local policy makers.